Krig och fred i vendel- och vikingatida traditioner - Rydving, Håkan; Olsson, Stefan (Stockholm Studies in Comparative Religion, 2016)
"What were the ideas about conflicts and conflict resolutions in the Nordic countries during the Vendel Period and the Viking Age? What role did i.e. gender and power hierarchies play in the conflicts? All of the contributing texts are, in one way or another, related to the theme 'war and peace'. They present new interpretations of some of the Old Scandinavian texts as well as of archaeological material: the runic inscription on the Eggja stone (Andreas Nordberg), texts about the fight between the god Thor and the giant Hrungnir (Tommy Kuusela), about the valkyries (Britt-Mari Näsström), about a phalos cult (Maths Bertell), about fylgjur, a type of beings regarded as related to the fate of a person (Eldar Heide), about enclosed areas for fights and battles (Torsten Blomkvist), about the defilement of sacred areas and places as a power strategy (Olof Sundqvist), about ritualisations of peace negotiations (Stefan Olsson), and about Ragnarök, the end and renewing of the world (Anders Hultgård). The book has been edited by Hakan Rydving and Stefan Olsson, both from the The Department of Archaeology, History, Cultural Studies and Religion (AHKR) at the University of Bergen. *** This book is published in Swedish: Vilka idéer om konflikter och konfliktlösningar hade man i Norden under vendel- och vikingatid (från ca 550 till ca 1100)? Hur uppfattades gudar som Oden och Tor och andra väsen som valkyrior och fylgjor kunna påverka krig och fred? Hur reglerades användningen av våld och hur utformades fredsprocesser? Vilken roll spelade kön och makthierarkier i konflikterna? Hur förhåller sig de förkristna skandinaviska föreställningarna om den sista striden till motsvarande kristna och forniranska traditioner? Det är några av de frågor som bidragen i den här boken diskuterar. Undersökningarna baseras i huvudsak på texter från den aktuella perioden och från tidig medeltid, men också på arkeologiskt material. De ger intressanta exempel på hur källorna till vendel- och vikingatida traditioner kan analyseras om man tar utgångspunkt i frågor om krig och fred. Boken har redigerats av Håkan Rydving och Stefan Olsson, båda verksamma vid Institutt for arkeologi, historie, kultur- og religionsvitskap (AHKR) vid Universitetet i Bergen."